Efficient Radar Forward Operator for Operational Data Assimilation within the COSMO-model - Zeng, Yuefei (Wissenschaftliche Berichte des Instituts für Meteorologie und Klimaforschung des Karlsruher Instituts für Technologie, 2013)
Doppler radars provide unique 3D information about precipitating clouds in high spatial and temporal resolutions. However, the observed quantities (reflectivity, Doppler velocity and polarization properties) are not directly comparable to the variables of numerical prediction models. In order to enable radar data assimilation, a comprehensive modular radar forward operator has been developed.